Real-world utilization of liquid biopsy for epidermal growth factor receptor (EGFR) testing in patients with metastatic non-small cell lung cancer (mNSCLC). Issue 28 (1st October 2022) - Shah, Anne; Apple, Jon; Ryan, Debra L.; de Silva, Kevin; Cai, Ling; Shenolikar, Rahul
Abstract : 402 Background: Tissue biopsy (TB) testing is the standard of care to guide the selection of targeted therapy in EGFRm patients with mNSCLC. However, liquid biopsy (LB) tests are increasingly important in assessing tumor genomics at mNSCLC diagnosis. This study assessed real-world utilization of LB for EGFR testing in 1L setting and its influence on 1L treatment decisions in mNSCLC patients. Methods: Adults newly diagnosed with mNSCLC from January 1, 2019 to May 31, 2021 and treated with 1L were identified from the Flatiron EMR database. LB utilization and patterns (either used alone or in combination with TB) were evaluated. "Concurrent" (TB & LB) testing was defined as patients with both test order dates prior to result dates for either test, while "sequential" (TB & LB) testing was defined as patients having one test's result date before the other test's order date. As patients could have multiple biomarker tests, the first two EGFR tests following diagnosis were evaluated. Results: Of 5, 036 patients that met the study criteria, 89.2% (N = 4, 494) had EGFR testing following diagnosis. Among those tested for EGFRm, 63.7% (N = 2, 864) had TB only, while 36.3% (N = 1, 630) had LB (LB only: 37.9%; concurrent: 36.1%; sequential: 26.0%). Around 90% of patients with LB had NGS testing (87.7% received LB testing within 90 days of diagnosis). Among patients who initiated 1L after EGFR testing, the median (IQR) time in days from testing to 1L initiation varied by testing patterns: LB only: 18 (12-30); concurrent: 29 (22-39); sequential: 28 (18-41). Disagreement in test results was 10.6% for patients who had conclusive test results for both TB and LB tests. Among concurrent EGFRm patients (N = 130), 21.5% initiated 1L after receiving LB results (and before TB results) and 60.0% after receiving both test results. Among patients with sequential LB followed by TB (N = 10), 80.0% of them initiated 1L after receiving LB results and before TB results (Table). Conclusions: In this real-world study among mNSCLC patients in a 1L setting, more than one-third used LB for EGFR testing, either alone or in combination with TB. Among LB patients, majority had NGS testing.Sequence of testing & initiation of 1L among EGFRm mNSCLC patients by testing patterns. Concurrent TB & LB (N = 130) Sequential TB & LB TB Only (N = 540) LB Only (N = 105) LB Followed by TB (N = 10) TB Followed by LB (N = 101) Initiated 1L prior to any test result, N (%) 13 (10.0%) 2 (20.0%) 14 (13.9%) 120 (22.2%) 25 (23.8%) Initiated 1L after LB test result but before TB result, N (%) 28 (21.5%) 8 (80.0%) 0 (0.0%) 80 (76.2%) †† Initiated 1L after TB test result but before LB result, N (%) 11 (8.5%) 0 (0.0%) 66 (65.3%) 420 (77.8%) † Initiated 1L after knowing both TB & LB test results, N (%) 78 (60.0%) 0 (0.0%) 21 (20.8%) † indicates patients who initiated 1L after TB test result and no LB test; †† indicates patients who initiated 1L after LB test result and no TB test.